Pengaruh Akuntabilitas Laporan Keuangan Pemerintah Daerah (LKPD) dan Kinerja Keuangan Pemerintah Daerah terhadap Tingkat Korupsi Pemerintah Daerah di Indonesia - Sapitri, Welia; Arza, Fefri Indra (Universitas Negeri Padang, 2024)
This study aims to examine the effect of accountability of local government financial reports in the form of audit opinion by BPK and local government financial performance (independence ratio, activity ratio, and growth ratio) on the level of corruption of local governments in Indonesia. This study uses a sample of financial reports of Regency / City Regional Governments in Indonesia that have been audited by BPK in 2020 and the KPK Annual Report in 2020. Based on the purposive sampling method, the total research sample was 507 financial reports of all Regency / City Regional Governments in Indonesia. Hypothesis testing in this study used logistic regression techniques. This study shows that audit opinion, independence ratio, activity ratio, and growth ratio have no significant effect on the level of corruption in Indonesia.